Penerapan Model Pembelajaran Think Pair Share (TPS) Untuk Meningkatkan Hasil Belajar Matematika - Lubis, Susi Sulastri; Nurdalilah; Rian Rinaldi (Journal Education Innovation (JEI), 2024)
This research aims to determine the direct effect of implementing "The Influence of the Think Pair Share (TPS) Learning Model on Student Mathematics Learning Outcomes on the Subject of Lines and Series at SMA Negeri 2 Siabu". The research method used is classroom action research using two cycles carried out in the first semester with Number Pattern Material. The population in this study was 59 students in class The class used as a sample is class XI MIPA-2 SMA at SMA Negeri 2 Siabu which will use the Think Pair Share (TPS) Learning Model in learning. The results obtained from this research are that the ability of students' learning outcomes in learning Mathematics through the Think Pair Share (TPS) learning model for class Fair” in cycle I, then increased to 88.55 in the “Good” category in cycle II. The results obtained in cycle II showed that the expected categories had been fulfilled, namely with an average score of 75 and classical completion of 75% of students getting a minimum score of Good